Fatal conveniences : the toxic products and harmful habits that are making you sick -- and the simple changes that will save your health - Olien, Darin (Harper Wave, an imprint of HarperCollinsPublishers, 2023)
"Fatal conveniences are the toxic products we routinely use and the unhealthy things we do that our culture and corporations have made us believe are safe and necessary for living well and efficiently. These things--from deodorant, cosmetics, dental floss, and sunscreen to laundry detergent, air fresheners, carpets, and crayons to candles, tea bags, cell phones, and chewing gum--are ubiquitous in daily life . . . and they are wreaking havoc on our health and our planet. The environmental toxins found in these products create a cascade of problems, including chemical sensitivities, auto-immune issues, obesity, chronic health diseases, and more."--